2005
DOI: 10.2214/ajr.185.1.01850095
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Stress First-Pass Contrast-Enhanced Myocardial Perfusion MRI Compared with Stress Myocardial Perfusion Scintigraphy

Abstract: The diagnostic accuracy of stress perfusion MRI acquired with saturation-recovery-prepared turbo FLASH was comparable with that of stress 201Tl SPECT. Stress first-pass contrast-enhanced MRI is a noninvasive technique that can be used as an alternative to stress myocardial perfusion scintigraphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 30 publications
4
52
0
1
Order By: Relevance
“…In our singlecenter studies, the diagnostic accuracy of stress perfusion MRI was superior to that of stress SPECT. 32,33 The area under the ROC curve for detection of significant CAD was 0.84-0.86 for stress perfusion MRI, significantly higher than that of stress perfusion SPECT (0.72-0.79). 32 In a recent multicenter, multivendor prospective trial by Schwitter et al, the diagnostic performance of stress perfusion MRI (area under the ROC curve 0.86±0.06) was better than that of stress perfusion SPECT (0.67±0.05, P=0.003), particularly in patients with 2-and 3-vessel disease.…”
Section: Circulation Journal Vol73 September 2009mentioning
confidence: 94%
“…In our singlecenter studies, the diagnostic accuracy of stress perfusion MRI was superior to that of stress SPECT. 32,33 The area under the ROC curve for detection of significant CAD was 0.84-0.86 for stress perfusion MRI, significantly higher than that of stress perfusion SPECT (0.72-0.79). 32 In a recent multicenter, multivendor prospective trial by Schwitter et al, the diagnostic performance of stress perfusion MRI (area under the ROC curve 0.86±0.06) was better than that of stress perfusion SPECT (0.67±0.05, P=0.003), particularly in patients with 2-and 3-vessel disease.…”
Section: Circulation Journal Vol73 September 2009mentioning
confidence: 94%
“…Sensitivities of 81-93% and specificities of 68-90% have been reported for stress first-pass perfusion MRI in the detection of clinically significant coronary artery disease (CAD) as defined at coronary angiography [9][10][11][12][13][14][15][16][17]. However, to the best of out knowledge, there are only three multicenter studies demonstrating the diagnostic performance of firstpass perfusion MRI for the detection of CAD [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sakuma et al (11,12) used saturation-recovery turbo FLASH sequence for detecting significant stenosis. They reported that in at least one coronary artery the sensitivity was 81.0%, specificity was 68.4%, positive predictive value was 73.9%, negative predictive value was 76.5%, and accuracy of stress perfusion MRI was 75.0%.…”
Section: Discussionmentioning
confidence: 99%